International Organizations in Global Social Governance - Martens, Kerstin; Niemann, Dennis; Kaasch, Alexandra (Global Dynamics of Social Policy, 2021)
International Organizations (IOs) are important actors within global social governance. They provide forums for exchange, contention and cooperation about social policies. Our knowledge about the involvement of IOs varies significantly by policy fields, and we know comparatively little about the specific roles of IOs in social policies. This volume enhances and systematizes our understanding of IOs in global social governance. It provides studies on a variety of social policy fields in which different, but also the same, IOs operate. The chapters shed light on IO involvement in a particular social policy field by describing the population of participating IOs; exploring how a particular global social policy field is constituted as a whole, and which dominant IOs set the trends. The contributors also examine the discourse within, and between, these IOs on the respective social policies. As such, this first-of-its kind book contributes to research on social policy and international relations, both in terms of theoretical substantiation and empirical scope.